The Social Housing Crisis and the Barriers to Developing Dementia-Friendly Communities in Chile - Jiménez, Daniel A.; Cancino-Contreras, Francisca (Frontiers in Public Health, 2021)
Interaction with living place and neighbourhood is one of the cornerstones for creating dementia-friendly communities (DFC). Chile has one of the largest proportions of older adults in Latin America and is currently facing an increase in the number of people with dementia. In this context, the Chilean government has launched a national strategy that involves actions in the health and social care system, including the promotion of DFC. From a multisectoral approach, social and environmental aspects involving engagement with local communities and access to social connections and services are directly related to urban policies. This perspective article focuses on urban aspects of social housing policy, such as placement, networks, affordability and the relationship between subsidy structure and adequate housing provision in a country with a qualitative housing deficit of around 1,200,000 units and where a large proportion of people with dementia and their families live in poverty. We identified several barriers to delivering appropriate environments for people living with dementia in relation to a twofold problem: a) the social housing subsidy displaces caregivers and/or older adults to satellite towns where social connections and access to services and urban equipment are lost; and b) people resisting displacement live in overcrowded neighbourhoods where dementia is a common problem. In both scenarios, a detrimental environment and social conditions directly affect the quality of life of elderly people living with dementia and their caregivers.